2017
DOI: 10.1155/2017/1914073
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors and the Risk of Periodontitis Development: Findings from a Systematic Review Composed of 13 Studies of Meta-Analysis with 71,531 Participants

Abstract: Purpose. This work aimed to synthesize the results of recent meta-analysis focusing on polymorphism in inflammatory mediators and its relation with the risk of periodontitis development. Materials and Methods. A systematic search was conducted using databases for publications prior to October 2016. Three examiners extracted data from articles with a clear association between polymorphisms in the inflammatory mediator gene and the development of periodontitis through meta-analysis using the fixed or randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 42 publications
0
53
0
3
Order By: Relevance
“…Polymorphisms of many interleukin genes have been significantly associated with the occurrence of periodontal disease [da Silva et al, 2017;Finoti et al, 2017], while variations in the TNFA and IL6 genes have been reported to contribute to the development of otitis media, as such genetic changes may result in alteration of the production of these cytokines, consequently leading to an altered inflammatory response and contributing to disease development [Emonts et al, 2007].…”
Section: Genesmentioning
confidence: 99%
“…Polymorphisms of many interleukin genes have been significantly associated with the occurrence of periodontal disease [da Silva et al, 2017;Finoti et al, 2017], while variations in the TNFA and IL6 genes have been reported to contribute to the development of otitis media, as such genetic changes may result in alteration of the production of these cytokines, consequently leading to an altered inflammatory response and contributing to disease development [Emonts et al, 2007].…”
Section: Genesmentioning
confidence: 99%
“…Periodontitis is a multifactorial disease; aside from interaction between periodontal pathogens and host immunoinflammatory response, genetic factors may be associated with the pathogenesis of periodontal disease [2,3]. The loss of clinical attachment (CAL) in periodontitis is caused by the destruction of periodontal tissues initiated by group(s) of Gram-negative and anaerobic bacteria that colonize the subgingival [4].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is an inflammatory disease of the supporting dental tissue that is initiated by specific microorganisms or groups of specific microorganisms, ultimately causing periodontal apparatus destruction by means of loss of clinical attachment (CAL) [1][2][3][4]. In addition, we have investigated the prevalence of periodontal diseases in Indonesia, finding that chronic periodontitis was the most common form of periodontal disease at 75.2%; a weak positive correlation was found between age and chronic periodontitis [5].…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 is a pro-inflammatory cytokine active in immune response against microbial agents. IL-1 induces chemokines and prostaglandins secretion, together with metalloproteinases production, enhancing, in turn, tissue destruction [57].…”
Section: Il-1bmentioning
confidence: 99%